Activation of the JAK-STAT Signaling Pathway after In Vitro Stimulation with IFN beta in Multiple Sclerosis Patients According to the Therapeutic Response to IFN beta - Hurtado-Guerrero, Isaac; Pinto-Medel, María-Jesús; Urbaneja, Patricia; Rodríguez-Bada, José Luis; León, Antonio; Guerrero, Miguel; Fernández-Fernández, Óscar; Leyva-Fernández, Laura; Oliver-Martos, Begoña (Public Library of Science, 2017)
Interferon beta (IFNß) is a common treatment used for multiple sclerosis (MS) which acts through the activation of the JAK-STAT pathway. However, this therapy is not always effective and currently there are no reliable biomarkers to predict therapeutic response. We postulate that the heterogeneity in the response to IFNß therapy could be related to differential activation patterns of the JAK-STAT signaling pathway. Our aim was to evaluate the basal levels and the short term activation of this pathway after IFNß stimulation in untreated and IFNß treated patients, as well as according to therapeutic response. Therefore, cell surface levels of IFNAR subunits (IFNAR1 and IFNAR2) and the activated forms of STAT1 and STAT2 were assessed in peripheral blood mononuclear cells from MS patients by flow cytometry. Basal levels of each of the markers strongly correlated with the expression of the others in untreated patients, but many of these correlations lost significance in treated patients and after short term activation with IFNß. Patients who had undergone IFNß treatment showed higher basal levels of IFNAR1 and pSTAT1, but a reduced response to in vitro exposure to IFNß. Conversely, untreated patients, with lower basal levels, showed a greater ability of short term activation of this pathway. Monocytes from responder patients had lower IFNAR1 levels (p = 0.039) and higher IFNAR2 levels (p = 0.035) than non-responders just after IFNß stimulation. A cluster analysis showed that levels of IFNAR1, IFNAR2 and pSTAT1-2 in monocytes grouped 13 out of 19 responder patients with a similar expression pattern, showing an association of this pattern with the phenotype of good response to IFNß (p = 0.013).
Keywords: Esclerosis múltiple - Tratamiento; Interferón; Multiple sclerosis; IFN beta; JAK-STAT Signaling Pathway